A clinical case study that raised ethical issues in a developing country. (September 2019) - Chinweokwu Onubogu, Uchenna
A 4-day-old female was admitted into a Nigerian Hospital, with neonatal tetanus, jaundice, and sepsis. Four days into the treatment, her clinical condition continued to deteriorate. The family requested to be discharged against medical advice on the grounds that the outcome of continued treatment may not be favorable with the possibility of neurological disability and the financial burden of continued treatment which could lead to catastrophic financial consequences for the rest of the family members. This is in line with the utilitarian moral principle in which, decisions are made based on the maximum number of individuals who would benefit from the outcome in spite of the fact that some individuals may be harmed by such decisions. The doctor's opinion was that continuing the child's treatment and protecting the child's right to survival could only happen with the baby remaining in hospital care. This is in line with the deontological ethical theory which judges an action based on it being morally correct irrespective of its actual consequence. The ethical issue arising here is, how appropriate is it to make decisions in the best interests of the child when the overall cost of that decision is weighing heavily on the interests of the larger society which in this case is the family. In conclusion, while professional medical ethics is the same in most countries, implementation of what is in the child's best interests varies according to the provisions made available by each country.